Determination of photon-driven charge transfer efficiency: drawbacks, accuracy and precision of different methods using Hematite as case of study - Bedoya-Lora,FE; Valencia-García,ME; Hankin,A; Klotz,D; Calderón,JA (Electrochimica Acta, 2022)
The electrochemical properties of photoelectrodes must be measured accurately and precisely to enable better comparisons between different materials. Along with the flat band potential, the interfacial charge transfer efficiency, which is the ratio between charge transfer rate at the photoelectrode surface and rate of charge carrier generation in the photoelectrode, can be used to predict the current density response at a given photon flux and electrode potential. The most widely used techniques for measuring charge transfer efficiencies are Photo-Electrochemical Impedance Spectroscopy (PEIS), current density ratios in the presence and absence of hole/electron scavengers, chrono-amperometry and Intensity Modulated Photocurrent Spectroscopy (IMPS). Charge transfer efficiencies can be estimated from PEIS and IMPS spectra either by using raw data (graphically), by fitting equivalent electrical circuits or by computing the Distribution of Relaxation Times (DRT). However, these techniques have their own drawbacks and impracticalities, that require researchers to make a choice between measuring accurately or pragmatically. Hitherto, the theoretical and experimental details of these techniques have not been summarised collectively and comprehensively. Here, we report the benefits and drawbacks, the accuracy, precision and best experimental recommendations when employing different techniques for photon-driven charge transfer efficiency determination.